Case Report: Zolbetuximab-induced gastritis with protein-losing gastroenteropathy and hypogammaglobulinemia: a case implicating IgA vasculitis - Yasuhiro Mitsui; Yasushi Sato; Ryo Shinomiya; Satoshi Sumida; Shota Fujimoto; Akiko Okada; Takeshi Mitsuhashi; Tomoyuki Kawaguchi; Kaizo Kagemoto; Yoshifumi Kida; Koichi Okamoto; Hisanori Uehara; et al. (Frontiers in Oncology)
Zolbetuximab (ZOL), a monoclonal antibody targeting Claudin-18.2, is a promising therapeutic agent for the treatment of advanced gastric cancer. We report the first case of ZOL-induced acute gastritis leading to protein-losing gastroenteropathy, characterized by severe hypogammaglobulinemia and hypoalbuminemia, possibly mediated by IgA vasculitis. A 41-year-old woman with metastatic Claudin-18.2-positive gastric cancer was treated with ZOL in combination with chemotherapy. On day 8 of the second treatment cycle, she developed severe gastrointestinal symptoms and immunologic abnormalities. Laboratory tests revealed marked hypogammaglobulinemia (IgG 193 mg/dL) and hypoalbuminemia (albumin 1.9 g/dL). Esophagogastroduodenoscopy showed severe acute gastritis, and biopsy specimens demonstrated infiltration of CD4+ lymphocytes into the stroma and CD8+ lymphocytes into both the epithelium and stroma, as well as IgA deposition along interstitial capillaries. Protein leakage from the stomach was confirmed by 99mTc-HSA-D scintigraphy. These findings suggest that ZOL-induced mucosal injury and increased vascular permeability, likely driven by an IgA-mediated vasculitic mechanism, contributed to the protein loss. The patient’s symptoms and laboratory abnormalities improved with supportive care. Upon ZOL rechallenge, gastrointestinal symptoms and protein loss recurred in a milder form, reinforcing a causal relationship. This case highlights a novel pathophysiological link between ZOL-induced gastritis and systemic immunoglobulin loss, underscoring the importance of careful monitoring of serum protein levels during ZOL therapy. Further studies are warranted to elucidate the immune-mediated mechanisms and optimize management strategies.